Imbalance in the blood antioxidant system in growth hormone-deficient children before and after 1 year of recombinant growth hormone therapy - Pankratova, Maria S.; Baizhumanov, Adil A.; Yusipovich, Alexander I.; Faassen, Maria; Shiryaeva, Tatyana Yu.; Peterkova, Valentina A.; Kovalenko, Svetlana S.; Kazakova, Tatiana A.; Maksimov, Georgy V. (PeerJ, 2015)
The aim of our study was to examine the effects of 12-month therapy with recombinant growth hormone (rGH) on the blood antioxidant system in children with growth hormone deficiency (GHD). Total antioxidant capacity (TAC) of plasma was measured by FRAP (ferric reducing antioxidant power or ferric reducing ability of plasma); activities of superoxide dismutase (SOD) and catalase (CAT) in erythrocytes were assessed; non-protein thiols (NT) and ceruloplasmin (CP) levels were also measured. These parameters were determined before and after 12 month of rGH treatment. Eleven treatment-naive prepubertal children with growth hormone deficiency were included in the study. Another 11 prepubertal children comprised a control group. Before rGH treatment, TAC of plasma and NT level in the control group were significantly lower (726 ± 196 vs. 525 ± 166 µmol/L, P = 0.0182 and 0.92 ± 0.18 vs. 0.70 ± 0.22 µmol/ml, P = 0.0319, before and after the therapy, respectively). The only parameter that significantly (19.6 ± 4.7 vs. 14.5 ± 3.4 Units/g Hb, P = 0.0396) exceeded the same in the control group after rGH therapy was SOD activity. However, none of the measured parameters of antioxidant system in GHD children, except for TAC (525 ± 166 vs. 658 ± 115 µmol/L, P = 0.0205), exhibited significant improvement toward the end of the 12-month treatment period, although non-significant changes in CAT activity and CP level were also observed. This work has demonstrated that some parameters of the blood antioxidant system are out of balance and even impaired in GHD children. A 12-month treatment with rGH resulted in a partial improvement of the antioxidant system.
Keywords: Blood antioxidant status; Total antioxidant capacity (TAC); Superoxide dismutase (SOD); Catalase; Non-protein thiol (NT) levels; Ceruloplasmin; Recombinant growth hormone (rGH) treatment; Children with growth hormone deficiency (GHD)